2016
DOI: 10.1111/ajo.12507
|View full text |Cite
|
Sign up to set email alerts
|

‘…a one stop shop in their own community’: Medical abortion and the role of general practice

Abstract: The application of these findings by relevant health services and agencies has the potential to increase provision of medical abortion services in general practice settings, better meeting the health-care needs of women seeking this service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 22 publications
3
18
0
1
Order By: Relevance
“…Our research found general agreement that abortion is an essential service which is consistent with recent Australian research from the state of Victoria [23]. However, most of the GPs interviewed did not want to be a MTOP provider and felt that it was a stigmatised service.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our research found general agreement that abortion is an essential service which is consistent with recent Australian research from the state of Victoria [23]. However, most of the GPs interviewed did not want to be a MTOP provider and felt that it was a stigmatised service.…”
Section: Discussionsupporting
confidence: 87%
“…This highlights the need for GP peer networks and information that strikes a balance between publicly available information and privacy concerns to improve referral pathways from GP non providers to GP MTOP providers and to a public hospital if required. In line with other studies, GP MTOP providers also noted the need to develop key relationships with local social workers, psychologists, women’s health services, pharmacists and ultrasound providers [23, 28]. …”
Section: Discussionsupporting
confidence: 68%
“…The interview covered participants' experiences providing abortion services, their role in the 2008 law reform, their views of both the intent and outcomes of abortion law reform, and remaining challenges. They were also asked about their experience of medical abortion and their views on the role of general practitioners in provision 19 20. Interviews were conducted by DN, and lasted between 30 minutes and 2 hours; de-identified audio-recordings were transcribed verbatim.…”
Section: Methodsmentioning
confidence: 99%
“…The legal differences and ambiguities in abortion laws across Australian jurisdictions, together with anti‐abortion views and the fear of stigma or harassment, can affect the willingness of doctors to provide abortions . Abortion provision remains predominantly confined to private clinics in metropolitan areas, and abortion access for women from Australia's regional and rural areas can therefore be highly restricted . One approach to improve this inequitable situation is to increase the use of medication abortion (MA) in the primary health care (PHC) sector.…”
Section: Introductionmentioning
confidence: 99%
“…This approach can complement two other currently applied MA provision models in Victoria: MA provided by Gateway Health, a primary health care service located in northeast Victoria, and MA provided through direct‐to‐consumer telemedicine . Although regional and rural GPs are at the forefront of providing comprehensive sexual and reproductive health care and are usually a woman's first point of contact with the health system, the uptake of MA by the GPs has been slow, even in Victoria where abortion is legal . Further, few primary health care nurses (PHCNs) are currently involved in the medication abortion process, a strategy that has globally become a key solution to improve women's access to safe abortion services .…”
Section: Introductionmentioning
confidence: 99%